2015
DOI: 10.1126/science.aad5575
|View full text |Cite
|
Sign up to set email alerts
|

Opening the window for aqueous electrolytes

Abstract: Lithium batteries can operate with a safer “water-in-salt” electrolyte [Also see Research Article by Suo et al. ]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 7 publications
0
62
0
Order By: Relevance
“…[217][218][219][220][221][222] Undoubtably, the most obvious benefit of this optimized electrolyte system is an increased variety of available cathode/anode materials comparing with the traditional type of ARLBs. However, only a few studies have been reported on ARLBs with hierarchitectures, especially constructed by 2D nanomaterials.…”
Section: Aqueous Rechargeable Lithium Batteriesmentioning
confidence: 99%
“…[217][218][219][220][221][222] Undoubtably, the most obvious benefit of this optimized electrolyte system is an increased variety of available cathode/anode materials comparing with the traditional type of ARLBs. However, only a few studies have been reported on ARLBs with hierarchitectures, especially constructed by 2D nanomaterials.…”
Section: Aqueous Rechargeable Lithium Batteriesmentioning
confidence: 99%
“…[18,19] Recently,s everal self-healing electronic devices have been fabricated. [20][21][22][23][24][25][26][27][28] However,LIBs that are capable of self-healing have not been realized owing to the difficulties in designing appropriate electrodes and battery structures to enable efficient self-healing for all the components simultaneously.A dditionally,c onventional organic electrolytes decompose rapidly in air once the LIBs are damaged, [29,30] which further increases the complexity to achieve the self-healing functionality.I ti so fb oth scientific and technological importance to explore this kind of LIB.The self-healing capability of the LIBs will be critical for wearable electronics in the near future.Herein, an ew family of self-healing aqueous LIBs is presented for the first time,tothe best of our knowledge,by designing aligned carbon nanotube (CNT) sheets loaded with LiMn 2 O 4 (LMO) and LiTi 2 (PO 4 ) 3 (LTP) nanoparticles on as elf-healing polymer substrate as electrodes and aqueous lithium sulfate/sodium carboxymethylcellulose (Li 2 SO 4 / CMC) as both gel electrolyte and separator. Thecooperation of self-healing polymer with the electrical and healing properties of the aligned CNT sheets electrode and Li 2 SO 4 / CMC gel electrolyte are key to achieve high flexibility and good recovery of electrochemical performance.Inparticular, the electrochemical storage capability was well maintained after several cutting and self-healing cycles.Thef abrication of the self-healing electrodes is shown in Figure 1a.Afree-standing self-healing polymer substrate (see the photographs and chemical structure in Figures S1-S3 of the Supporting Information) was prepared by am odified Leiblersm ethod.…”
mentioning
confidence: 99%
“…Intercalated lithium could directly react with the electrolyte in the first cycle, which triggers the formed solid electrolyte interface . This interfacial layer serves a critical role in many commercial batteries . Solid electrolyte interface layers can decompose at a lower temperature, and then the intercalated lithium will directly react with the electrolyte .…”
Section: Discussionmentioning
confidence: 99%
“…25 This interfacial layer serves a critical role in many commercial batteries. 26 Solid electrolyte interface layers can decompose at a lower temperature, and then the intercalated lithium will directly react with the electrolyte. 16 According to Biensan et al, 27 the exothermic reactions between intercalated lithium and electrolyte or binder were the main heat sources of thermal runaway.…”
Section: Temperature Variation At Different Socsmentioning
confidence: 99%